2011
DOI: 10.3136/fstr.17.537
|View full text |Cite
|
Sign up to set email alerts
|

Tetragenococcus halophilus MN45 Ameliorates Development of Atopic Dermatitis in Atopic Dermatitis Model NC/Nga Mice

Abstract: We investigated the inhibitory effects of oral administration of Tetragenococcus halophilus MN45 (MN45) isolated from miso on the development of atopic dermatitis (AD) using NC/Nga AD model mice. NC/Nga mice were fed a diet containing 0.05% or 0.5% MN45 (0.05% or 0.5% MN45 groups) or lacking MN45 (control group). Mice were sensitized and boosted with picryl chloride by topical application once per week. IgE production in serum, clinical score and ear thickness in both MN45 groups were significantly suppressed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…These results suggest that miso strengthens immune robustness and prevents both autoimmunity and infectious diseases, resulting in the maintenance of good health. LAB isolated from miso has been reported to suppress allergies [41,42], and other studies have reported that it enhances immunity, in part, by activating B cells [13]. In this study, we found that miso regulates immunity in the same way as LAB isolated from miso.…”
Section: Plos Onesupporting
confidence: 69%
“…These results suggest that miso strengthens immune robustness and prevents both autoimmunity and infectious diseases, resulting in the maintenance of good health. LAB isolated from miso has been reported to suppress allergies [41,42], and other studies have reported that it enhances immunity, in part, by activating B cells [13]. In this study, we found that miso regulates immunity in the same way as LAB isolated from miso.…”
Section: Plos Onesupporting
confidence: 69%
“…However, we observed a low prevalence of T. halophilus in humans, and its detection was associated with high stool salinity. This discovery therefore suggested that T. halophilus was part of the human digestive microbiota in some individuals, in whom its role on human health should be further considered ( Masuda et al., 2008 , Ohata et al., 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, T. halophilus has been shown to produce organic acids, amino acids and flavoring compounds during the fermentation of salty foods ( Udomsil et al., 2010 , Udomsil et al., 2017 , Lee et al., 2018 ). Moreover, T. halophilus has been credited from beneficial effects on human health, in particular an immunomodulatory effect leading to improvement of atopic diseases ( Masuda et al., 2008 , Ohata et al., 2011 ). Despite the widespread presence of T. halophilus in salty foods, this species has never been described in humans in the many studies which have proven the presence of halophilic bacteria in the human microbiota ( Oxley et al., 2010 , Seck et al., 2018 , Khelaifia et al., 2017 , Khelaifia and Raoult, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, T. halophilus may be important for the production of organic acids, amino acids, and flavouring compounds during fermentation of salty foods (Jong-Hoon et al, 2017). Additionally, T. halophilus has health benefits, including immunomodulatory properties and amelioration of atopic diseases (Ohata et al, 2011). It is, therefore, recommended to use T. halophilus as a starter culture to improve the flavour, taste, and quality of fermented soybean products (Chun et al, 2019).…”
Section: Discussionmentioning
confidence: 99%